Layered double hydroxide modified with linseed compounds for polyurethane elastomer nanocomposites - Kumar, S.; Malas, A.; Kumar Das, Ch. (Polimery, 2012)
Layered double hydroxides (LDHs) are a class of layered inorganic materials, containing basic layers of metal hydroxides. Between these layers anions and water molecules are accommodated. Interlayer anion can be replaced by wide range of organic and inorganic anions and this key feature of LDH opens new fields of applications. In this study magnesium and aluminum based LDH was modified with linseed compounds using the regeneration method. Modified LDH samples were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), high resolution transmission electron microscopy (HR-TEM), scanning electron microscopy (SEM) and field emission scanning electron microscopy (FE-SEM). XRD results indicate that anionic spacer has gone inside the gallery space, which is evident from increased interlayer spacing. FT-IR study suggests the presence of spacer moiety in modified LDH. From FE-SEM study, it was observed that the shape and texture of LDH platelets have changed (they were hexagonal and smooth before modification). Unmodified and modified LDH were applied to prepare polyurethane nanocomposites (PUR/LDH and PUR/LLDH, respectively). Nanocomposite PUR/LLDH was characterized by better mechanical and thermal properties in comparison with PUR/LDH and neat polyurethane.